Reproductive variables and risk of benign breast diseases: a case-control study - Hardy, Ellen E. (1990)
The purpose of the study was the identification of risk factors for benign breast diseases (BBD); 257 women with BBD diagnosed through pathological anatomy or citology and a matched control for each were studied. Subjects were selected at The State University of Campinas Hospital and at a private clinic. To enter the study cases had to have a first diagnosis of BBD between October 1979 and August 1984. The following BBD were considered: dysplasia, fibroadenoma, cystic disease, papilloma and ductal ectasia. Reproductive variables were studied as risk factors, including menstrual ovulatory cycles. The date on which the BBD was diagnosed was defined as the index date. For controls, data were considered up to when they had reached the same age as the matched case on the occasion of her diagnosis. Nulliparity was a risk factor for BBD. First birth at or above age 30 was a protective factor. Women who had used contraceptive pills for two or more years had a significantly lower risk than those who had never used them. The number of menstrual ovulatory cycles was not found to be associated with the risk of BBD. The results obtained from the study of Brazilian women confirm some of the conclusions found in the literature, mainly those that associate some reproductive variables with the risk of BBD. A few of these variables are also confirmed as risk factors for breast cancer.